2018
DOI: 10.1021/acssuschemeng.8b01532
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Electrochemical Properties of LiFePO4 Cathode Using Waterborne Lithiated Ionomer Binder in Li-Ion Batteries with Low Amount

Abstract: The poor conductivity of olivine structure LiFePO4 led to inevitable hindered electrochemical performances and restricted their uses in Li-ion batteries. To overcome the problem, introduction of conductive agents that bind with LiFePO4 active material is a universal solution. In this paper, a novel waterborne lithiated ionomer binder (PSBA-Li)for Li-ion batteries was originally designed and assembled with the low addition of 1.5% of a LiFePO4 cathode, showing a high areal capacity of 2.0 mAh cm–2. During lith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…The attached Li + on the binder chains could help shorten the pathway of the free Li + to the particles' surface and enhance the Li + conductivity. 24 Additionally, the introduction of some specic polar functional groups into the 3D crosslinked binder were proved to effectively enhance the transport of Li + and e À . 11 For instance, Zhang et al prepared a double-helix-structure water-based binder consisting of abundant charged functional groups (hydroxyl and carboxylate), which were benecial to wrap binder chains tightly on the surfaces of the particles and conductive additives, and to contribute a compact interconnected electric network.…”
Section: Introductionmentioning
confidence: 99%
“…The attached Li + on the binder chains could help shorten the pathway of the free Li + to the particles' surface and enhance the Li + conductivity. 24 Additionally, the introduction of some specic polar functional groups into the 3D crosslinked binder were proved to effectively enhance the transport of Li + and e À . 11 For instance, Zhang et al prepared a double-helix-structure water-based binder consisting of abundant charged functional groups (hydroxyl and carboxylate), which were benecial to wrap binder chains tightly on the surfaces of the particles and conductive additives, and to contribute a compact interconnected electric network.…”
Section: Introductionmentioning
confidence: 99%
“…14 Recently, the lithiated polymers have been developed as effective binders to improve the electrochemical performances of LIBs ether for LiFePO 4 and LiMn 2 O 4 cathode or graphite/Si anode. 15,[16][17][18][19][20][21][22][23] These lithiated polymers can provide extra lithium-ion, which facilitates the ion transport and thus promotes the high rate performances of the cells. In summary, most of these polymers are the lithiated sulfonate polymers, including perfluorosulfonate, poly(etherether-ketone) and poly(vinylidenefluoride hexafluoro propylene).…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21] Additionally, Yuan et al reported the lithiated carboxylate polymer binders with different functions, such as, self-healing and crosslinking. 15,[22][23] Although the lithiated polymers can improve the rate performance of LIBs ether cathode or anode, they also exhibit brittle property due to the metal salt on polymer chain. [24][25][26] Previously, we reported a composite of lithiated PAA and terpene resin as a water soluble binder for LiFePO 4 cathode, 27 which demonstrates some advantages of lithiated PAA, such as, extra lithium-ion compensation for lithiumion loss, and strong adhesion capability due to the carboxylate functional groups.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations